Penerapan Metode Analisis 3R Dalam Penilaian Kelayakan Pembiayaan Investasi di BTN KCS Bandung - Defi Elza Purwaningsih; Badriyatul Huda; Arif Mulyawan Thoriq; Bahmid I Magi (Jurnal Dimamu, 2023)
Based on observations, that the background of this research is the number of customers who have decreased due to lack of accuracy in analyzing return, repayment, and risk bearing abilities conducted by BTN KCS Bandung which affect the assessment of the feasibility of investment financing at the bank. This study aims to determine how the application of the method of analysis of return, repayment, and risk bearing ability in assessing the feasibility of investment financing in BTN KCS Bandung. The object of research in this thesis is to assess the feasibility of investment financing at BTN KCS Bandung. The type of research is descriptive qualitative with primary data type and uses data collection technique in the form of observation, interviews, literature study, and triangulation. While the data analysis techniques are data collection, reduction, data presentation, and conclusions. The results showed that there were three things that became the application of the return analysis method in assessing the feasibility of investment financing at BTN KCS Bandung, there were two things that became the application of the repayment analysis method in assessing the feasibility of investment financing at BTN KCS Bandung, and there were two things that became teh application risk bearing ability analysis method in assessing the feasibility of financing in BTN KCS Bandung.